The effect of triangular prismatic elements on the hydraulic performance of stepped spillways in the skimming flow regime: an experimental study and numerical modeling. Issue 2 (8th February 2022) - Roushangar, Kiyoumars; Akhgar, Samira; Shahnazi, Saman
Abstract: The stepped spillway is a cost-effective hydraulic structure to dissipate the energy of large water flow over the spillway of a dam. In this study, the focus was placed on the effects of triangular prismatic elements (TPEs) on the hydraulic performance of a stepped spillway. Nine stepped spillway models were experimentally and numerically investigated with different shapes and layouts of TPEs. To adopt a proper turbulent model, RNG k - ε and standard k - ε models were utilized. The computational model results satisfactorily simulated the complex flow over the stepped spillway of experiment cases, including velocity distributions and pressure profiles on the step surfaces. The results indicated that the installation of TPEs on stepped spillways can be an effective way to reduce cavitation effects. Installing TPEs on stepped spillways increased the energy dissipation rate up to 54%. The performance of stepped spillways was improved when TPEs were spaced more closely together. Furthermore, the relationships between the roughness coefficient ( f ) and the ratio of the critical depth to the step roughness ( yc / k ) were obtained with high accuracy using the experimental data. HIGHLIGHTS: The Flow-3D model was applied to examine the effects of triangular prismatic elements (TPEs) on the hydraulic performance and energy dissipation of stepped spillways. Two types of TPEs with different spacing were experimentally investigated for varied flow rates. Stepped spillways with TPEs are more efficient in terms of energy dissipation.